PENGARUH KESEMPATAN PROMOSI, IKLIM ORGANISASI DUKUNGAN ATASAN DAN KETERLIBATAN KERJA TERHADAP KEPUASAN KERJA DIMEDIASI CAREER PLATEAU (Studi pada PT.Telkom Wilayah Pekalongan) - Yekti Andriyani, 12.52.02.0030 (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of this study was to analyze the effect of promotion opportunities, Organizational Climate, Supervisor Support, Job Involvement on Job Satisfaction  Career Plateau mediated. The method used is an explanatory study, the population in this study were all employees PT.Telkom Pekalongan region some 126 people. Respondents in this study only 100 people out of 126 questionnaires were distributed. Analysis of data using multiple linear regression. The study results indicate that the independent variable, promotion opportunities, job involvement, Career plateau has a direct influence on job satisfaction, supervisor support and organizational climate has no effect on job satisfaction, supervisor support and involvement while working negatively affect the career plateau. Career plateau is not proven to mediate supervisor support and job involvement on job satisfaction in other words that career plateau direct effect on job satisfaction. Keywords :      Promotional opportunities, Organizational Climate, Supervisor Support, Job Involvement, Career Plateau, Job Satisfaction